Problems of legal regulating of the civil legislation on trade secrets: comparative legal analysis - Nukusheva, А.А.; Kudryavtseva, L.V.; Ivanchenko, I.A. (Bulletin of the Karaganda University “Law Series”, 2019)
The article considers the institution of trade secret as one of the most effective measures to ensure infor-mation security, analyzes the legal regulation of trade secrets in modern civil science in Kazakhstan and Rus-sia, as well as in other countries. The problem of trade secret as an object of civil rights does not lose its relevance in the modern world, which is due to the rapid informatization and intellectualization of production, an increase in the knowledge-intensive economy and the great commercial value of know-how, ideas and projects. The authors define the concept, types and signs of trade secret; explore the features of civil legal liability for violation of trade secret in the Republic of Kazakhstan, the Russian Federation and several other countries. The article establishes the need for further improvement of the legislation of the Republic of Kazakhstan and the Russian Federation on trade secret, explores the mechanism for protecting the right to trade secret and the specifics of protecting the right to trade secret in corporate, labor and contractual relations, due to the existence of a trade ecret regime for the circulation of such information. Theoretical and practical significance are in the content of this article, contributing to the deepening of scientific knowledge about the legal nature of civil rights to trade secret.